Efficacy of organic matter and some bio-inoculants for the management of root-knot nematode infesting tomato - Khan, Neha; Safiuddin, Dr; Rizvi, Rose; Ansari, Rizwan Ali; Mahmood, Irshad; Sumbul, Aisha; Tiyagi, Sartaj A (International Journal of Environment, 2015)
Efficiency of an organic matter like Tagetes erecta and bioinoculants Azotobacter chroococcum and Glomus fasciculatum was investigated in tomato cultivar ‘Pusa Ruby’ when inoculated individually as well as concomitantly for the management of the root-knot nematode, Meloidogyne incognita in terms of growth parameters such as plant length, fresh and dry weights, chlorophyll content, per cent pollen fertility and mycorrhization. Greatest reduction in the numbers of second-stage juveniles in soil, number of root-galls, egg-masses and nematode multiplication was recorded with combined application of T. erecta and bio-inoculants A. chroococcum and G. fasciculatum as compared to untreated control and other treatments. Similarly, the greatest improvement in the plant growth and biomass of tomato was noted in the same treatments. However, individual inoculation of these bio-inoculants and organic fertilizers also showed significant enhancement but was less as compared to combined treatment. A. chroococcum was found most effective against disease incidence followed by G. fasciculatum and T. erecta. Parameters like NP and K contents were significantly enhanced in those plants which received combined treatments of organic matter and bio-inoculants. Azotobacter was found more efficacious against nematodes than Glomus fasciculatum. Organic matter also influenced the activity of bio-inoculants, more with the Azotobacter than G. fasciculatum. DOI: http://dx.doi.org/10.3126/ije.v4i2.12643 International Journal of Environment Vol.4(2) 2015: 206-220